Introduction: plurilingual expatriate teachers in higher education. Issue 3 (3rd July 2019) - Melo-Pfeifer, Sílvia; Yanaprasart, Patchareerat
ABSTRACT: Higher education institutions have been progressively dealing with issues related to the internationalization of their faculties, in order to increase their position in rankings and their attractiveness in a high competitive market. In such a context, institutions are expected to recruit international students and teachers. This special issue focus on the roles and the impacts of plurilingual expatriate teachers in Higher Education as perceived and described by institutions, colleagues and students, in different contexts (Canada, Germany, Italy, Luxembourg, The Netherlands, Portugal and Switzerland). Under the label 'international', synonymous with modernity and attractiveness, English, often portrayed as 'the language of internationalization'. The aim of this special issue is to pay a closer look not only on the policy of English as academia lingua franca, but also on other linguistic contexts and constellations.